Inuit Identities, Language, and Territoriality - Patrick, Donna (Diversité urbaine, 2008)
This paper provides a framework for understanding the social complexity of the linkages between language, identity, and territoriality (or attachments to place). Drawing on qualitative research among Inuit in the Canadian Arctic and in Ottawa, it discusses Inuit identities in relation to the role played by local, regional, national, and global processes in constructing Inuitness and the transformation of Indigenous identities nationally and globally. The paper argues that although Inuktitut is being supported by institutional and political structures in Nunavik and Nunavut, English and French have become increasingly important in daily Northern life. At the same time, Inuit migration to Southern cities has offered new challenges and established new priorities in the fostering of the plurilingualism necessary for urban Inuit life. Cet article offre un cadre pour comprendre la complexité sociale des liens entre la langue, l’identité et la territorialité (ou l’attachement au lieu). Reposant sur une recherche qualitative faite parmi les Inuits de l’Arctique canadien et d’Ottawa, j’y discute des identités inuites en relation avec le rôle joué par les processus locaux, régionaux, nationaux et mondiaux dans la construction de l’« Inuitness » et la transformation des identités indigènes sur les plans national et mondial. Cet article mettra en lumière que, bien que l’inuktitut soit soutenu par des structures institutionnelles et politiques au Nunavik et au Nunavut, l’anglais et le français sont devenus de plus en plus importants dans la vie quotidienne nordique. En même temps, la migration inuite vers les villes du Sud a présenté de nouveaux défis et a établi de nouvelles priorités dans la formation du plurilinguisme nécessaire à la vie inuite urbaine.